Effects of different rearing temperatures on muscle development and stress response in the early larval stages of acipenser baerii - Aidos, Lucia; Valente, Luisa M. Pinheiro; Sousa, Vera; Lanfranchi, Marco; Domeneghini, Cinzia; Di Giancamillo, Alessia (European Journal of Histochemistry, 2017)
The present study aims at investigating muscle development and stress response in early stages of Siberian sturgeon when subjected to different rearing temperatures, by analysing growth and development of the muscle and by assessing the stress response of yolk-sac larvae. Siberian sturgeon larvae were reared at 16°C, 19°C and 22°C until the yolk-sac was completely absorbed. Sampling timepoints were: hatching, schooling and complete yolk-sac absorption stage. Histometrical, histochemical and immunohistochemical analyses were performed in order to characterize muscle growth (total muscle area, TMA; slow muscle area, SMA; fast muscle area, FMA), development (anti-prolif erating cell nuclear antigen -PCNA or anticaspase) as well as stress conditions by specific stress biomarkers (heat shock protein 70 or 90, HSP70 or HSP90). Larvae subjected to the highest water temperature showed a faster yolk-sac absorption. Histometry revealed that both TMA and FMA were larger in the schooling stage at 19°C while no differences were observed in the SMA at any of the tested rearing temperatures. PCNA quantification revealed a significantly higher number of proliferating cells in the yolk-sac absorption phase at 22°C than at 16°C. HSP90 immunopositivity seems to be particularly evident at 19°C. HPS70 immunopositivity was never observed in the developing lateral muscle.